The Effect of Financial Risk Management and Income Diversification towards Bank Performance (Evidence form the Commercial Banking Sector) - Alaeddin, Omar; Thabet, Ahmed; Shawtari, Fekri Ali (International Journal of Engineering and Technology, 2018)
This paper aims to report the effects of a study on the relationship between financial risk management practices and income diversification towards Palestinian commercial banks profitability. The method involved in this research is administering a questionnaire to 11 commercial banks listed on the Palestinian Monetary Authority website and the respondents were those in the risk management department on banks such as chief executive officers (CEOs), chief risk officers (CROs), chief financial controllers, general managers, risk managers, and bank employees at departments related to risk management in Palestinian commercial banks. Also, Panel model analysis was used to estimate the moderation role of income diversification on profitability. It was found that the Palestinian commercial banks managers have a significant level of understanding of risk and risk management practices. In light of the interaction between financial risk management practices (FRMP) with Non-Interest Income Ratio (NIDR) on banks profitability is positive significant (Î²=.074, p Ë‚ 0.05). Therefore, the result indicates that FRMP with NIDR has a significant effect on the organizational financial performance.